1970
DOI: 10.13057/biodiv/d070101
|View full text |Cite
|
Sign up to set email alerts
|

Soil Fungi in an Over-burned Tropical Rain Forest in Bukit Bangkirai, East Kalimantan

Abstract: A study was conducted in Bukit Bangkirai forest, East Kalimantan, to understand the impact of forest fire on the existence of soil fungi. Three permanent plots were used for the research, i.e. undamaged plot (K), lightly damaged plot (LD), and heavily damaged plot (HD). Each plot was 1 ha and divided into 100 sub-plots (10 m x 10 m). For observation of soil fungi, in the center of the five randomly selected sub-plots from each plot was made a sampling plot (2 m x 2 m). After removing the organic matter surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
0
3
0
6
Order By: Relevance
“…Di antara 15 marga jamur tersebut, Aspergillus merupakan marga jamur yang banyak ditemukan, yaitu 13 jenis diikuti Penicillium dan Fusarium masing-masing adalah 7 dan 3 jenis. Aspergillus flavus Link ex Gray dan A. niger van Tieghhem ditemukan pula di tanah hutan bekas terbakar di Bukit Bangkirai, Kalimantan Timur (Suciatmih, 2006b) dan tanah hutan bekas terbakar di Wanariset Samboja, Kalimantan Timur (Suciatmih, 2006a). Gliocladium virens Miller, Gidden & Foster dilaporkan pula terisolasi dari lumpur mangrove Okinawa, Jepang (Ito dan Nakagiri, 1997a), rizosfir tanaman mangrove Okinawa, Jepang (Ito dan Nakagiri, 1997b), tanah hutan bekas terbakar di Bukit Bangkirai, Kalimatan Timur (Suciatmih, 2006b) dan tanah mangrove Muara Angke, Jakarta (Nakagiri et al, 2005 Nakagiri et al (2005) dari areal mangrove Muara Angke, Jakarta.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…Di antara 15 marga jamur tersebut, Aspergillus merupakan marga jamur yang banyak ditemukan, yaitu 13 jenis diikuti Penicillium dan Fusarium masing-masing adalah 7 dan 3 jenis. Aspergillus flavus Link ex Gray dan A. niger van Tieghhem ditemukan pula di tanah hutan bekas terbakar di Bukit Bangkirai, Kalimantan Timur (Suciatmih, 2006b) dan tanah hutan bekas terbakar di Wanariset Samboja, Kalimantan Timur (Suciatmih, 2006a). Gliocladium virens Miller, Gidden & Foster dilaporkan pula terisolasi dari lumpur mangrove Okinawa, Jepang (Ito dan Nakagiri, 1997a), rizosfir tanaman mangrove Okinawa, Jepang (Ito dan Nakagiri, 1997b), tanah hutan bekas terbakar di Bukit Bangkirai, Kalimatan Timur (Suciatmih, 2006b) dan tanah mangrove Muara Angke, Jakarta (Nakagiri et al, 2005 Nakagiri et al (2005) dari areal mangrove Muara Angke, Jakarta.…”
Section: Hasil Dan Pembahasanunclassified
“…Aspergillus flavus Link ex Gray dan A. niger van Tieghhem ditemukan pula di tanah hutan bekas terbakar di Bukit Bangkirai, Kalimantan Timur (Suciatmih, 2006b) dan tanah hutan bekas terbakar di Wanariset Samboja, Kalimantan Timur (Suciatmih, 2006a). Gliocladium virens Miller, Gidden & Foster dilaporkan pula terisolasi dari lumpur mangrove Okinawa, Jepang (Ito dan Nakagiri, 1997a), rizosfir tanaman mangrove Okinawa, Jepang (Ito dan Nakagiri, 1997b), tanah hutan bekas terbakar di Bukit Bangkirai, Kalimatan Timur (Suciatmih, 2006b) dan tanah mangrove Muara Angke, Jakarta (Nakagiri et al, 2005 Nakagiri et al (2005) dari areal mangrove Muara Angke, Jakarta. A. corymbifera dan G. butleri ditemukan pula di tanah hutan bekas terbakar di Bukit Bangkirai, Kalimantan Timur (Suciatmih, 2006) dan tanah hutan bekas terbakar di Wanariset , Kalimantan Timur (Suciatmih, 2006a).…”
Section: Hasil Dan Pembahasanunclassified
“…Forest and land fire causes the dying, decreasing, and disturbing the population of the soil biology diversity (microorganisms and microorganisms), which are essential in the forest and land ecosystem, especially to maintain and improve the soil fertility (quality). (Barrow 1991, Suciatmih 2006, Saharjo and Nurhayati 2006, Saharjo et al 2011 . Impacted soil biology (especially soil fauna) by forest fire needs significant time to recovery.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the soil has a low rate of salt and lime (Ca +2 ) could exclude their negative effect on the activity of soil microorganisms. Suciatmih (2006) found that a significant positive correlation existed between the fungal population and the total organic carbon content. Waid (1960), listed temperature, humidity, CO 2 , oxygen concentration, size of the soil pores, longevity of fungal mycelium, interaction between soil fauna and soil fungi and soil reaction as factors that may influence growth and production of the mycelium of fungi in the soil.…”
Section: Discussionmentioning
confidence: 93%
“…According to Suciatmih (2006), the forest fire leads to a reduction and possibly an elimination of soil fungi. Chet (1984) reported studies on mode of action of Trichoderma used for biological control against Rhizoctonia solani in the case of cotton and strawberry cultivation, the results highlighted the importance of mycoparasitism phenomenon in the effectiveness of Trichoderma.…”
Section: Discussionmentioning
confidence: 99%